Teacher Self-Efficacy as a Mediator Between Social Support and Well-Being: The Role of Demographics in Islamic Private Elementary Schools Toward SDG 3 - Lely Ika Mariyati; Eko Hardi Ansyah; Mohd Nazri Abdul Rahman; Dwi Nastiti; Syaefnah Rachmawati (Universitas PGRI Yogyakarta, 2026)
This study examines the role of teacher self-efficacy as a mediator between social support and occupational well-being among teachers in Islamic private elementary schools, within the framework of SDG 3 (Good Health and Well-being). A quantitative, cross-sectional design was employed, involving 221 teachers from nine districts in East Java Province, Indonesia. Data were collected using validated scales for occupational well-being, social support, and teacher self-efficacy, and analyzed using structural equation modeling (SEM). The results confirm that social support significantly influences teachers' occupational well-being, but only through the full mediation of teacher self-efficacy (p < 0.05). The direct effect of social support on well-being was not significant. Furthermore, demographic factors—including age, gender, income, educational background, and certification status—did not show significant moderating effects on either self-efficacy or occupational well-being (p > 0.05). These findings underscore that self-efficacy is a critical internal mechanism translating external support into improved well-being, regardless of demographic differences. The study contributes to the JD-R Model and Self-Determination Theory by extending their application to faith-based educational settings. Practically, enhancing teacher self-efficacy through targeted training and supportive policies is essential for improving teacher welfare, which in turn supports the achievement of SDG 3 at the institutional and community levels. Keywords: social support, teacher self-efficacy, occupational well-being, islamic school